2021
DOI: 10.1186/s12986-020-00527-y
|View full text |Cite
|
Sign up to set email alerts
|

Milk consumption and multiple health outcomes: umbrella review of systematic reviews and meta-analyses in humans

Abstract: In order to recapitulate the best available evidence of milk consumption and multiple health-related outcomes, we performed an umbrella review of meta-analyses and systematic reviews in humans. Totally, 41 meta-analyses with 45 unique health outcomes were included. Milk consumption was more often related to benefits than harm to a sequence of health-related outcomes. Dose–response analyses indicated that an increment of 200 ml (approximately 1 cup) milk intake per day was associated with a lower risk of cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 143 publications
(157 reference statements)
2
68
1
3
Order By: Relevance
“…Nonetheless, recent studies have shown that milk and dairy, regardless of their fat content, may have a beneficial effect on metabolic and cardiometabolic health [9,10]. With regard to the effects of milk on brain health, although some studies indicated a positive impact of dairy consumption on cognitive performance and in reducing the risk of dementia [11,12], most of the results are still controversial [13][14][15]. In particular, little is known about the mechanisms linking milk/dairy intake and cognitive performance, and, in general, there is a lack of knowledge of the efficacy of individual milk nutrients on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, recent studies have shown that milk and dairy, regardless of their fat content, may have a beneficial effect on metabolic and cardiometabolic health [9,10]. With regard to the effects of milk on brain health, although some studies indicated a positive impact of dairy consumption on cognitive performance and in reducing the risk of dementia [11,12], most of the results are still controversial [13][14][15]. In particular, little is known about the mechanisms linking milk/dairy intake and cognitive performance, and, in general, there is a lack of knowledge of the efficacy of individual milk nutrients on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of milk intake on the risk of neurodegenerative diseases have been widely investigated. Observational studies have shown that milk intake is associated with a reduced risk of multiple sclerosis (MS) [ 3 , 4 ] and Alzheimer’s disease (AD) [ 5 , 6 ], but with an increased risk of Parkinson’s disease (PD) [ 5 , 7 , 8 , 9 ]. The association between milk intake and amyotrophic lateral sclerosis (ALS) is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Выполняемый анализ ассоциаций проводится как c моделями питания [3,4], характеристиками энергетического и нутриентного статуса [5][6][7][8], так и с отдельными группами пищевых продуктов, охватывая как продукты ежедневно формирующие рацион (молочные изделия, фрукты и овощи, мясо и др.) [9][10][11][12][13][14][15][16][17][18], так и продукты "праздничного стола" (кондитерские изделия, сахарсодержащие напитки, переработанная продукция) [19]. Интерес исследователей привлекает вклад в формирование ожирения как сырьевых продуктов [9,14,20], так и продуктов разной степени переработки [6, 10-12, 19, 21], а при анализе молочной продукции -еще и процентное содержание молочного жира [13].…”
Section: Associations Of Dietary Patterns and Abdominal Obesity In The Adult Population Results Of The Russian Epidemiological Esse-rf Stunclassified
“…Поэтому анализ уровня потребления продуктов молочной группы и наличия ожирения вызывает интерес во многих исследованиях [10][11][12][13][14][15][16][17][18]. Однако результаты анализов очень разнятся: от снижения риска АО [10,12,[14][15][16] и отсутствия различий [9,10] -до положительных ассоциаций с отдельными видами молочной продукции [17]. Аналогичные полученным в настоящем исследовании результаты в отношении более высокого потребления молока, кефира и йогурта женщинами с АО были отмечены и в другом российском исследовании [11], выполненном на результатах "Выборочного наблюдения рациона питания россиян", проведенного в 2013г [27].…”
Section: Discussionunclassified